A-256 Literacy Level May Mediate the Relationship Between an Individual's Ethnicity and Letter Fluency Ability. (17th August 2022) - Khan, Humza; Bing-Canar, Hanaan; Stocks, Jane K; Lapitan-Moore, Franchezka; DeBoer, Adam B; Durkin, Nicole M; Cerny, Brian M; Jennett, Kyle J; Soble, Jason R; Resch, Zachary J
Abstract: Objective: Previous research suggests that literacy level may be a better predictor of cognitive performance than years of education in minoritized groups. Although literacy tests remain a mainstay in the context of neuropsychological evaluations due to their role in the estimation of premorbid intellectual functioning, there is relatively little research examining the role of literacy in the relationship between ethnicity and cognitive performance. This study examined whether literacy level influences the relationship between ethnicity and letter fluency ability. Method: This cross-sectional study included 64 adult patients consecutively referred for outpatient neuropsychological evaluation within a large, Midwestern academic medical center. The sample was 54.7% male, 43.8% White, 56.3% Black, with Mage of 57.8 years (SD=11.7) and Meducation of 12.6 years (SD=2.5). A mediation analysis was performed using Hayes' PROCESS macro within SPSS to evaluate whether literacy, as measured by the Test of Premorbid Functioning (TOPF), mediated the association between ethnicity (dichotomized as Black/White) and letter fluency via raw scores from the F/A/S trials. Results: The main model of the mediation analysis was significant, F (4, 51) = 13.89, p <.001, R2 = .521. After accounting for age and years of education, there was a significant mediation effect of literacy on the relationship between ethnicity and letter fluency (B = .740, SE = .143, t = 5.19, p <.001). Conclusion(s): In sum, this study provided evidence that literacy level helps explain the letter fluency performance differences observed between Black and White patients.